2020
DOI: 10.3390/met10070942
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Migration Inhibition of Tin by Disodium Hydrogen Phosphate in Water Drop Test

Abstract: The inhibition effect of Na2HPO4 on the electrochemical migration (ECM) of pure tin was investigated by means of water drop testing and surface characterizations. The effects of concentration of Na2HPO4 and applied direct current (DC) bias voltage on the ECM were also studied. Results showed that the mean time to failure caused by ECM decreased with the increasing bias voltage. Upon addition of relative high concentrations of Na2HPO4, Na2HPO4 can react with metallic tin or tin ions to form a protective film on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Another corrosion inhibitor introduced to inhibit ECM of Sn recently was disodium hydrogen phosphate (Na 2 HPO 4 ). 143 It was reported that upon adding 500-1000 mg l −1 of Na 2 HPO 4 to 1 mM NaCl, a compact film mainly consisting of Sn, O and P formed on Sn anode and slowed down the rate of anodic dissolution. It is important to note that the ECM inhibitors are different from the corrosion inhibitors.…”
Section: Strategies For Ecm Inhibitionmentioning
confidence: 99%
“…Another corrosion inhibitor introduced to inhibit ECM of Sn recently was disodium hydrogen phosphate (Na 2 HPO 4 ). 143 It was reported that upon adding 500-1000 mg l −1 of Na 2 HPO 4 to 1 mM NaCl, a compact film mainly consisting of Sn, O and P formed on Sn anode and slowed down the rate of anodic dissolution. It is important to note that the ECM inhibitors are different from the corrosion inhibitors.…”
Section: Strategies For Ecm Inhibitionmentioning
confidence: 99%